Konsep Perancangan Infotainment Map Pesantren Daarut Tauhiid - Azany, Genta; Persada, Satria Indra Praja (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2024)
Daarut Tauhiid Islamic Boarding School is one of the famous Islamic boarding schools in Bandung which is currently located on Gegerkalong Girang street. Daarut Tauhiid has a very large open area and has many institutional buildings and facilities spread across various areas. However, students and visitors are often confused about finding the location of the building/facility they want to visit. With this problem, a design is needed to inform the Daarut Tauhiid Islamic Boarding School area such as the location of the building/facility through infotainment map media. The purpose of this design is to facilitate and help students and visitors who are interested in finding the location of the building/facility they want to visit in the Daarut Tauhiid Islamic Boarding School area with creative visual information. With the infotainment map, it is hoped that students and visitors will no longer have difficulty finding the location of the building/facility they want to visit, by getting creative visual information.